Assessment of Up-Grading Nursing Students’ Knowledge and Practice towards Short Peripheral Catheters (SPCs) Care at Al-Quds University - Maraka, Nida’; Moshashe, Fadwa (International Journal of Innovative Research in Medical Science, 2021)
A short peripheral catheter is a medical device, a plastic tube inserted into a vein. A cross-sectional descriptive study was conducted to assess knowledge and practice towards short peripheral catheter care among first-year up-grading nursing students at Al-Quds University in Palestine. A convenience sample of 90 students filled questionnaires that showed they were newly- graduated with 46.1% having low experience and an inadequate knowledge level and 57.5% having a moderate practice level, with an inverse correlation between knowledge and practice. Sessions in the simulation laboratory about peripheral catheter care should be conducted to enhance quality and safety.